2022
DOI: 10.3389/fnins.2022.974673
|View full text |Cite
|
Sign up to set email alerts
|

EEG emotion recognition based on cross-frequency granger causality feature extraction and fusion in the left and right hemispheres

Abstract: EEG emotion recognition based on Granger causality (GC) brain networks mainly focus on the EEG signal from the same-frequency bands, however, there are still some causality relationships between EEG signals in the cross-frequency bands. Considering the functional asymmetric of the left and right hemispheres to emotional response, this paper proposes an EEG emotion recognition scheme based on cross-frequency GC feature extraction and fusion in the left and right hemispheres. Firstly, we calculate the GC relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Granger causality test revealed that there was connectivity from the right precentral gyrus to the left precentral gyrus and dorsal anterior cingulate cortex, which affected the internet gaming disorder severity. Zhang et al [ 78 ] proposed the cross-frequency Granger causality feature extraction and fusion in both hemispheres for EEG emotion recognition. This proposed Granger causality had higher accuracy than the same-frequency band Granger causality features.…”
Section: Literature Review On the Application Of Granger Causalitymentioning
confidence: 99%
“…Granger causality test revealed that there was connectivity from the right precentral gyrus to the left precentral gyrus and dorsal anterior cingulate cortex, which affected the internet gaming disorder severity. Zhang et al [ 78 ] proposed the cross-frequency Granger causality feature extraction and fusion in both hemispheres for EEG emotion recognition. This proposed Granger causality had higher accuracy than the same-frequency band Granger causality features.…”
Section: Literature Review On the Application Of Granger Causalitymentioning
confidence: 99%
“…Then, each 60 s EEG signal was divided into segments with a window length of and an overlap time of . Our previous work [ 34 ] has shown that the best recognition performance can be achieved when the and are 3 s and 1.5 s, respectively. EEG signals of four frequency bands were extracted using STFT.…”
Section: The Proposed Gc-f-gcn Scheme For Eeg Emotion Recognitionmentioning
confidence: 99%
“…The higher the GC value, the stronger the causality between the corresponding EEG signals. On the contrary, smaller GC values indicate weaker causal relationships or connections caused by noise [ 34 ]. Figure 2 c shows that the number of causal values in the original GC matrix of EEG signals at each frequency band is .…”
Section: The Proposed Gc-f-gcn Scheme For Eeg Emotion Recognitionmentioning
confidence: 99%
“…Sun R, Cheng AS K, Chan C, et al ( 2015): This study explores the possibility of using electroencephalography to track gaze position, which may help develop virtual eye tracking technology [21] . Chen D, Huang H, Bao X, et al ( 2023): This study proposes an attention recognition method based on EEG signals, which combines time-domain, frequency-domain, and nonlinear dynamic features [22] . Wang P, Cao X, Zhou Y, et al ( 2023): This review article summarizes recent research on decoding neural activity related to limb movement trajectories, which may help develop assistive and rehabilitation strategies for motion impaired users [23] .…”
Section: Introductionmentioning
confidence: 99%